Muslim & science religious orthodoxy and the struggle for rationality - Hoodbhoy, Pervez Amirali (Vanguard, 1991)
A compelling and provocative analysis of the relationship between the scientific spirit and orthodoxy and scope of one of the great monotheistic religions.